Casing wall static pressure distribution behavior in a centrifugal compressor with asymmetric inlet/outlet structures. (February 2019) - Yang, Ce; Zhang, Hanzhi; Yang, Dengfeng; Lao, Dazhong; Yang, Changmao
Asymmetric structures of the bent inlet pipes and outlet volute are typically adopted in centrifugal compressors. By using asymmetric inlet/outlet structures, the uniformity of the compressor's internal flow field in the circumferential direction will be changed. The static pressure distribution behavior around the casing wall is significantly influenced by the coupling effect of the bent inlet pipe and outlet volute. In the present work, three compressors were numerically and experimentally investigated. One compressor had a straight inlet pipe, and the other two had bent inlet pipes. Seventy-two static pressure sensors were mounted around the casing wall to obtain the static pressure distribution at different flow rates for three rotational speeds. The results show that at high rotational speeds with large flow rate conditions, when the static pressure waves induced by the bent pipe and volute act on the same circumferential position, the casing wall static pressure will be increased at the corresponding position. Furthermore, this high static pressure will further influence the static pressure values at other circumferential positions and leads to a more nonuniform circumferential static pressure distribution. Near the design flow rate, when the high static pressure strips, which are induced by both the bent pipe and volute impact different circumferential positions, the high static pressure strip induced by the volute will be weakened. As a result, the high static pressure strip induced by the volute cannot propagate upstream into the impeller. At small flow rate under designed rotational speed, the influence of the volute tongue on the casing pressure distribution will be enhanced. At small flow rate under low rotational speed, the casing pressure distributions of the three models were almost the same because the secondary flow effect of the bent pipe diminishes as the flow rate reduces.